Pre-admission anticoagulant therapy and mortality in hospitalized COVID-19 patients: A retrospective cohort study. Issue 208 (December 2021) - van Haaps, Thijs F.; Collard, Didier; van Osch, Frits H.M.; Middeldorp, Saskia; Coppens, Michiel; de Kruif, Martijn D.; Vlot, Eline A.; Douma, Renée A.; ten Cate, Hugo; Juffermans, Nicole P.; Gritters, Niels; Vlaar, Alexander P.; et al.
Highlights: Hypercoagulability is a hallmark of COVID-19 patients. It is unknown if pre-admission anticoagulant improves patient outcomes. We studied 380 anticoagulant users and 380 matched controls with COVID-19. Pre-admission anticoagulation was not associated with mortality and ICU admission.